Can foreigners offer civil resistance to the authorities of the host country? A critical reevaluation of “civil resistance” in the fields of civil resistance studies and Hannah Arendt studies - Bragdon, Thomas (HannahArendt.net, 2024)
The paper discusses the emergence of noncitizen protest movements in European Union countries over the past three decades, focusing on movements like the Sans-Papiers in Paris and We Are Here in Amsterdam. These movements engage in nonviolent actions to challenge the host country’s laws while petitioning for citizenship. The paper explores the complexities of categorizing these actions as civil protest or civil disobedience, highlighting the performative effects of nonviolent actions and the categorizations with which they are labeled. The paper delves into the tension between the human rights of all individuals and the legal protection of civil rights only within state territories. Exploring the "right to have rights" concept, it argues that efficacy in civil protest is closely tied to the willingness of state authorities to listen to protestors’ demands. The paper suggests that the efficacy of noncitizen protests should be analyzed within the context of antagonism theory, distinguishing between the political and politics. The paper ultimately contributes to the discourse on the efficacy of civil protest in challenging legal systems and pursuing political change.